Analiza Rozkładu Naprężeń Wokół Otworów w Grubościennych Powłokach Walcowych - Zirka, A.I.; Sawczenko, W.I. (Engineering Transactions, 1972)
Experimental results are shown concerning the stress concentration problem for thick-walled cylindrical shells weakened by circular cavities, their axes being slant or perpendicular to the axis of the shell. The sheII is loaded by internal pressure. The corresponding three-dimensional state of stress is analysed by means of photo-elastic epoxy resin models. A number of practical conclusions arc drawn from the results obtained and from their comparison with theoretical analysis of the same problem.